1991
DOI: 10.1213/00000539-199103000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Succinylcholine on the Pharmacodynamics of Pipecuronium and Pancuronium

Abstract: To study the effects of succinylcholine on subsequent pharmacodynamics of nondepolarizing muscle relaxants, a comparative pharmacodynamic study was carried out in patients having balanced anesthesia (thiopental, fentanyl, nitrous oxide/oxygen) in whom equipotent doses of pipecuronium (80 micrograms/kg) and pancuronium (100 micrograms/kg) were given with or without prior administration of succinylcholine (1 mg/kg). Fifty-two patients were randomly assigned to one of the following four groups: 1, pancuronium (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…Our finding suggests that even the intubating dose of succinylcholine induces the phase II block and thereby increases the pancuronium-induced neuromuscular block during halothane anesthesia. This potentiation by halothane may explain the differences among the previous reports [1][2][3] on the interaction between succinylcholine and pancuronium.…”
contrasting
confidence: 61%
“…Our finding suggests that even the intubating dose of succinylcholine induces the phase II block and thereby increases the pancuronium-induced neuromuscular block during halothane anesthesia. This potentiation by halothane may explain the differences among the previous reports [1][2][3] on the interaction between succinylcholine and pancuronium.…”
contrasting
confidence: 61%
“…Dubois et al 10 demonstrated that prior administration of succinylcholine shortened the onset time of pancuronium and pipecuronium but did not modify the clinical duration. In his study, the nondepolarizing neuromuscular blocking agents pipecuronium and pancuronium were administrated before full succinylcholine recovery, and the twitch height was 75% of the control level.…”
Section: Discussionmentioning
confidence: 99%
“…These were seen in patients maintained with halothane-nitrous oxide anaesthesia (Scott & Norman 1989). Pipecuronium may similarly be associated with bradycardia (Dubois et al 1991), as well as decreased cardiac output, even in the absence of bradycardia (Wierda et al 1990a).…”
Section: Bradyarrhythrniasmentioning
confidence: 96%
“…Potentiation of small doses of atracurium (0.15 mglkg) following suxamethonium has been demonstrated (Stirt et al 1983) while large doses (0.24 mglkg) of doxacurium are not potentiated by prior suxamethonium administration (Katz et al 1988). A recent study failed to demonstrate significant potentiation of large (> ED95) doses of pancuronium or pipecuronium following suxamethonium (Dubois et al 1991). Other studies have demonstrated increased block intensity following pancuronium 0.02 mg/kg or tubocurarine 0.1 mg/kg.…”
Section: Other Muscle Relaxantsmentioning
confidence: 99%
See 1 more Smart Citation